2004
DOI: 10.1248/bpb.27.384
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Factors to Decrease Bioavailability of Cyclosporin A in Rats with Gentamicin-Induced Acute Renal Failure

Abstract: Focusing on the disposition of cyclosporin A (CsA) in the liver and intestine, effects of gentamicin-induced acute renal failure (ARF) on the decreased oral bioavailability of CsA were evaluated in rats. The area under the CsA concentration-time curve (AUC) in ARF rats after oral administration (5 mg/kg) significantly decreased by 43% as compared to the control, while the apparent oral clearance significantly increased by 76% of the control. The portal AUC of CsA in ARF rats with bile flow decreased by 67% as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 20 publications
2
21
0
Order By: Relevance
“…In the rats, hepatic function was not impaired, as judged from the laboratory data, whereas increases in the values of serum creatinine and BUN indicated an appreciable impairment of renal function by the high-AMB treatment (Table 2). However, the increases of serum creatinine and BUN were not large compared with the increases of about 3-to 5-fold and 2-to 5-fold in model rats with gentamicin-or glycerol-induced renal failure, respectively [22][23][24]. Therefore, we considered that the AMB-induced renal impairment was not great even in the high-AMB group, and may have had only a slight influence on the excretion of CyA, which is metabolized mainly by CYP3A.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In the rats, hepatic function was not impaired, as judged from the laboratory data, whereas increases in the values of serum creatinine and BUN indicated an appreciable impairment of renal function by the high-AMB treatment (Table 2). However, the increases of serum creatinine and BUN were not large compared with the increases of about 3-to 5-fold and 2-to 5-fold in model rats with gentamicin-or glycerol-induced renal failure, respectively [22][23][24]. Therefore, we considered that the AMB-induced renal impairment was not great even in the high-AMB group, and may have had only a slight influence on the excretion of CyA, which is metabolized mainly by CYP3A.…”
Section: Discussionmentioning
confidence: 72%
“…There are some reports indicating that the disposition kinetics of CyA is influenced by renal failure in rats. Shibata et al [22] reported that CYP3A and P-gp in liver and intestine are not likely to be involved in lowering the oral bioavailability of CyA in gentamicin-induced acute renal failure, and that a change in bile function is responsible for the marked decrease. Huang et al [23] reported that the expression level of P-gp in rats with glycerol-induced acute renal failure was increased 2.5-fold in the kidney, but not in the liver or brain.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al (2007) described a CyA LC-MS assay for use in monkey and rat plasma, although cyclosporine C was used as IS. Similarly Shibata et al (2004) reported a method using cyclosporine D as IS; as mentioned above, neither of these two IS is available commercially. In the current method, amiodarone was employed as IS.…”
Section: Discussionmentioning
confidence: 99%
“…For research purposes, the specific measurement of CyA is possible using one of a number of valuable highperformance liquid chromatographic (HPLC) methods (Burckart et al, 1990;Chimalakonda et al, 2002;McBride et al, 1989). More specific and sensitive liquid chromatography-mass spectrometry (LC-MS) methods have been reported for the measurement of CyA in various matrices, although many incorporate solid phase extraction (Zaater et al, 2005) or commercially unavailable internal standards (IS) such as cyclosporine C and D (Li et al, 2007;Shibata et al, 2004;Simpson et al, 1998), which can pose challenges to their widespread use.…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism is still unclear. On the other hand, it has been reported that CyA absorption decreased in rats with several drug-induced acute renal failure, and that decreased bile secretion was the main reason for reducing the absorption of CyA in gentamicin-induced acute renal failure rats [4,5]. Therefore, it is speculated that renal injury after CRT affects the PK of CyA.…”
Section: Introductionmentioning
confidence: 99%